2002
DOI: 10.1089/10430340252769770
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Gene Delivery and Targeted Expression to HepatocytesIn Vivoby Improved Lentiviral Vectors

Abstract: Safe and efficient genetic modification of liver cells could enable new therapies for a variety of hepatic and systemic diseases. Lentiviral vectors are promising tools for in vivo gene delivery. Previous data suggested that recruitment into the cell cycle was required for transduction of hepatocytes in vivo. We developed an improved vector design that enhanced nuclear translocation in target cells and significantly improved gene transfer performance. Using the new vector and a panel of internal promoters, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
183
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(193 citation statements)
references
References 34 publications
9
183
1
Order By: Relevance
“…Third-generation HIV-1 vectors lacking complement inhibitor proteins were prepared by transient transfection according to published procedures 34 using a mixture of four plasmids in the following amounts per 10 cm dish: pMDLg/pRRE (Gag/Pol expression plasmid) at 6.5 mg, pRSV-Rev 34 at 2.5 mg, Transfer Vector (pRRL.sin.CMV.eGFP.ppt.pre or pRRL.sin.CM-V.eGFP.pre) 35 at 10 mg, and 3.5 mg of envelope plasmid (pMD2.VSVG-Env or pMD2.AcNPV.Env 3 or pMD2.Ampho.Env 36 ). For vectors with complement inhibitor proteins, a fifth plasmid (pMD2-DAF, pMD2-MCP or pMD2-CD59) was added to the transfection reaction at 10 mg per plate.…”
Section: Production Of Pseudotyped Lentiviral Vectors With and Withoumentioning
confidence: 99%
“…Third-generation HIV-1 vectors lacking complement inhibitor proteins were prepared by transient transfection according to published procedures 34 using a mixture of four plasmids in the following amounts per 10 cm dish: pMDLg/pRRE (Gag/Pol expression plasmid) at 6.5 mg, pRSV-Rev 34 at 2.5 mg, Transfer Vector (pRRL.sin.CMV.eGFP.ppt.pre or pRRL.sin.CM-V.eGFP.pre) 35 at 10 mg, and 3.5 mg of envelope plasmid (pMD2.VSVG-Env or pMD2.AcNPV.Env 3 or pMD2.Ampho.Env 36 ). For vectors with complement inhibitor proteins, a fifth plasmid (pMD2-DAF, pMD2-MCP or pMD2-CD59) was added to the transfection reaction at 10 mg per plate.…”
Section: Production Of Pseudotyped Lentiviral Vectors With and Withoumentioning
confidence: 99%
“…These observations are in agreement with an earlier study where VSV-G-pseudotyped HIV vectors were found to mainly target the spleen, liver and bone marrow of mice injected i.v. 33,34 Discussion Previous evaluation of HIV-1 lentivectors following systemic delivery have demonstrated long-term expression of the transgene for up to 1 year, depending on the transgene and host. [33][34][35] An alternative to HIV-1 is the EIAV-based vector, which has been developed, in part, because HIV-1 is a human pathogen and as a result may face extra hurdles in clinical use.…”
Section: Eiav Vector For Systemic Delivery Of Proteinsmentioning
confidence: 96%
“…33,34 Discussion Previous evaluation of HIV-1 lentivectors following systemic delivery have demonstrated long-term expression of the transgene for up to 1 year, depending on the transgene and host. [33][34][35] An alternative to HIV-1 is the EIAV-based vector, which has been developed, in part, because HIV-1 is a human pathogen and as a result may face extra hurdles in clinical use. In addition to this, the potential advantages of EIAV are its relative simplicity compared to HIV-1, the inability of the parent virus to replicate in human cells and the nonlethal nature of the infection in its natural host, the genus Equidiae.…”
Section: Eiav Vector For Systemic Delivery Of Proteinsmentioning
confidence: 96%
“…40,41 Stimulation of hepatocytes to drag them in the cell cycle greatly improved liver transduction as well as modification of lentivectors such as inclusion of the central purine tract to achieve better transduction. [42][43][44] However, it turned out as well that immune response against the transgene product was elicited when large batches of lentivectors were administered to animals, thus precluding long-term expression of the transgene. 45 It was therefore required to use liver-specific promoters to circumvent induction of immune response after in vivo delivery of lentiviral vectors.…”
Section: Lentiviral Vectorsmentioning
confidence: 99%